Q. 115.0( 1 Vote )

# Solve the following differential equations: Given Differential equation is: ……(1)

Let us assume z = x + y

Differentiate w.r.t x on both sides we get,  ……(2)

Substitute(2) in (1) we get, Bringing like variables on same side (i.e., variable seperable technique) we get, e–zdz = dx

Integrating on both sides we get,

∫e–zdz = ∫dx

We know that:

(1) ∫adx = ax + C

(2)  –e–z = x + C

x + e–z + C = 0

Since z = x + y we substitute this,

x + e–(x + y) + C = 0

The solution for the given Differential Equation is x + e–(x + y) + C = 0.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Interactive Quiz on DIfferential CalculusFREE Class  Functional Equations - JEE with ease48 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 